Substance use, sexual behaviour and prevention strategies of Vancouver gay and bisexual men who recently attended group sex events - Rich, Ashleigh J (Cult Health Sex, 2015)
Group sex events are epidemiologically important part of some gay and bisexual men's sexual culture in Canada. Associated with condomless anal intercourse and polysubstance use, such events have been cited as disproportionally contributing to HIV infection rates. We analysed questionnaire data from the Momentum Health Study in Vancouver, Canada to understand substance use, sexual behaviour, psychosocial variables (Sexual Sensation Seeking, Sexual Escape Motivation, and Treatment Optimism), and HIV prevention strategies (sero-sorting, strategic positioning, avoiding anal sex, disclosure, treatment as prevention) of men attending such events, which were defined as group (n≥4 partners) sex parties, blackout events, and darkrooms. Analysis by multivariable logistic regression compared men attending group sex events within the past 6 months (n=180) with non-attendees (n=539). Results showed that attendees reported 1) significantly higher use of sex drugs and alcohol consumption, 2) higher scores on the Sexual Sensation Scale, more anal sex partners, greater odds of any condomless anal sex with sero-discordant partners, and greater odds of reporting fisting and sex toy use, and 3) different prevention practices that varied by HIV-serostatus. Findings are interpreted in light of the importance of pleasure, sociality, and HIV/STI prevention strategies associated with group sex events. Findings contribute to the development of appropriate education and intervention for attendees.